2020
DOI: 10.1161/strokeaha.120.030481
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Hospital Admissions for Transient Ischemic Attack, Mild, and Moderate Stroke During the COVID-19 Era

Abstract: Background and Purpose: Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, doctors and public authorities have demonstrated concern about the reduction in quality of care for other health conditions due to social restrictions and lack of resources. Using a population-based stroke registry, we investigated the impact of the onset of the COVID-19 pandemic in stroke admissions in Joinville, Brazil. Methods: Patients admitted after the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
247
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(281 citation statements)
references
References 17 publications
(17 reference statements)
29
247
3
2
Order By: Relevance
“…We observed a decrease by nearly one quarter in the number of patients admitted to our primary stroke center with stroke or TIA from a mean-rate of 95.9 (±6.3) per month between January 2019 and February 2020 to 74 (±12.7) in March/April 2020. Our observation is in line with numerous reports of decreased stroke rates during the pandemic from North America ( 4 , 9 , 10 ), Canada ( 5 ), and Brazil ( 6 ). In addition, a decrease in the usage of the RAPID-software, a tool used to assess infarct volume in case of acute stroke symptoms, was observed by mid-March 2020 ( 11 ) and telestroke services were less frequently used ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed a decrease by nearly one quarter in the number of patients admitted to our primary stroke center with stroke or TIA from a mean-rate of 95.9 (±6.3) per month between January 2019 and February 2020 to 74 (±12.7) in March/April 2020. Our observation is in line with numerous reports of decreased stroke rates during the pandemic from North America ( 4 , 9 , 10 ), Canada ( 5 ), and Brazil ( 6 ). In addition, a decrease in the usage of the RAPID-software, a tool used to assess infarct volume in case of acute stroke symptoms, was observed by mid-March 2020 ( 11 ) and telestroke services were less frequently used ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our hypothesis is strengthened by the fact that we observed unchanged rates of hemorrhagic stroke during the pandemic, which are usually accompanied by a more severe disability compared to ischemic strokes. This is further underlined by a retrospective analysis from Brazil also demonstrating unchanged rates of hemorrhagic stroke during the pandemic compared to pre-pandemic numbers and reporting an unchanged rate of severe strokes ( 6 ). In line with this, a multicenter analysis from Northern California reports decreased stroke rates in the early pandemic and even more severe strokes and large vessel occlusions ( 4 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, a report from Brazil has suggested that the COVID-19 outbreak coincided with a reduction in transient, mild, and moderate strokes. 8 There were no cases of symptomatic stroke among the 285 patients diagnosed with COVID-19 (including 12 deaths) during the study period. 9 A previous study of 214 COVID-19 patients (severe disease rate 41.1%) admitted to three centers in Wuhan, China, reported that 36.4% of them had some neurological symptoms, including 5.7% and 0.8% of patients presenting with severe and nonsevere cerebrovascular disease, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…A completely different observation, however, is the decreasing admission rate for acute neurological disorders, especially acute ischemic stroke that has been reported in temporal association with the pandemic and lockdown measures. 1,2 A decline in emergency department (ED) presentations during the pandemic has also been reported in several countries and across different disciplines. [3][4][5][6] In contrast, pre-COVID-19 assessments have documented a constant rise in the number of patients seeking evaluation and treatment in ED due to neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%